Neck-brain integrated ultrasound as a noninvasive screening tool to identify morphological features of middle cerebral artery disease. (December 2022) - Zhang, Jie; Wang, Shouchun; Chen, Ying; Li, Cong; Wang, Lijuan
Abstract: Background and aims: Endovascular treatment is suitable for middle cerebral artery (MCA) with focal lesion. Therefore, accurate evaluation of the morphological features of MCA disease is critical. Ultrasonography is commonly used to screen for MCA lesions. However, there are few studies on lesion length. Using ultrasonography, we aimed to prospectively evaluate MCA disease with focal stenosis, long stenosis, focal occlusion, and long occlusion. Methods: Patients with symptomatic MCA disease scheduled for digital subtraction angiography were enrolled. The ultrasonic parameters recorded included mean flow velocity at MCA (VMCA ) and extracranial internal carotid artery (VICA ), bilateral VMCA ratio, bilateral VICA ratio, and MCA flow continuity. Results: A total of 278 MCAs were included. Compared to normal vessels, the bilateral VMCA ratio increased in the focal stenosis group and decreased in the long lesion and focal occlusion groups (all p < 0.05); the VICA and bilateral VICA ratio decreased in the long lesion group (all p < 0.01), and there was no significant difference in the focal lesion group (all p > 0.05). The optimal cut-offs were bilateral VMCA ratio <0.80 to predict long lesions and focal occlusions (sensitivity: 0.898, specificity: 0.975), and bilateral VICA ratio <0.84 to predict long lesions (sensitivity: 0.704, specificity: 0.879). The sensitivity and specificity to predict long occlusions were 96.7% and 94.8%, respectively, in the absence of MCA flow continuity. Conclusions: Neck-brain integrated ultrasound is an appropriate screening method for identifying MCA lesions with different morphologies. Endovascular treatment might not be recommended when bilateral VICA ratio <0.84 in patients with MCA lesions. Graphical abstract: Image 1 Highlights: Ultrasonography is appropriate to screen middle cerebral artery (MCA) lesions with different morphology. Endovascular treatment might not fit for MCA lesion with bilateral VICA ratio <0.84. Low-velocity criteria could predict MCA with long stenosis or occlusion by ultrasound.